Exploring the role of mTOR pathway in aging and age-related disorders - Raghuvanshi, Komal; Raghuvanshi, Disha; Kumar, Dinesh; Nepovimova, Eugenie; Valko, Marian; Kuca, Kamil; Verma, Rachna (EXCLI journal, 2025)
Aging is a highly intricate biochemical process. There is strong evidence suggesting that organismal aging, age-dependent diseases, and cellular senescence are related to the mammalian target of rapamycin (mTOR) signaling pathway. The signaling pathway of mTOR has become a prominent regulatory hub, managing crucial cellular activities that significantly affect lifespan and longevity. The mTOR is involved in controlling cell growth and metabolism in response to both internal and external energy signals as well as growth factors. The interaction between mTOR and cellular homeostasis is crucial in the aging process. This extensive review summarizes the most recent findings on mTOR inhibitors in the context of aging, highlighting their complex interactions with cellular systems, effect on longevity, and potential as therapeutic approaches for age-related diseases. Rapamycin and rapalogs (analogs of rapamycin), which have been proven to be effective mTOR inhibitors, have the ability to reduce the aging process in several model species while also enhancing metabolic health and stress responses. Despite cellular factors, mTOR inhibitors have revealed a potential path for therapeutics in age-related illnesses. These results suggest mTOR inhibitors as potential therapies to address the complex aspects of age-related diseases. However, obstacles stand in the way of clinical translation. Further research is required to improve dosing protocols, reduce potential side effects, and target mTOR inhibitors precisely at specific tissues. In summary, the mTOR signaling pathway is an important node in the intricate web of aging and its associated disorders.
Keywords: mTOR; rapamycin; mTOR inhibitors; anti-aging interventions; aging